2008
DOI: 10.1186/1471-2229-8-123
|View full text |Cite
|
Sign up to set email alerts
|

Identification of precursor transcripts for 6 novel miRNAs expands the diversity on the genomic organisation and expression of miRNA genes in rice

Abstract: Background: The plant miRNAs represent an important class of endogenous small RNAs that guide cleavage of an mRNA target or repress its translation to control development and adaptation to stresses. MiRNAs are nuclear-encoded genes transcribed by RNA polymerase II, producing a primary precursor that is subsequently processed by DCL1 an RNase III Dicer-like protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 52 publications
2
39
1
Order By: Relevance
“…On the other hand, we obtained more than one precursor for the miRNAs 482, 159 etc. as reported in rice [34]. In addition, we observed single precursor gave rise to two distinct miRNAs.…”
Section: Discussionsupporting
confidence: 59%
“…On the other hand, we obtained more than one precursor for the miRNAs 482, 159 etc. as reported in rice [34]. In addition, we observed single precursor gave rise to two distinct miRNAs.…”
Section: Discussionsupporting
confidence: 59%
“…antisense-miR444 loci were found in our data (see Supplemental Table 3 online). Precursors of the miR159/319 family are relatively long, and it has been proposed that miR159a generates an additional miRNA, miR159a.2, from same arm of a precursor (Lacombe et al, 2008). We found that miR159c, miR159f, miR319a, and miR319b loci also produce other miRNAs that are similar to miR159a.2 in sequence, and we designated them as miR159cf.2, miR319a.2, and miR319b.2.…”
Section: Evaluation Of Annotated Mirnasmentioning
confidence: 87%
“…japonica) (Goff et al, 2002;Yu et al, 2002). Small RNAs have also been extensively discovered in rice Jones-Rhoades and Bartel, 2004;Sunkar and Zhu, 2004;Liu et al, 2005;Sunkar et al, 2005;Luo et al, 2006;Lacombe et al, 2008;Lu et al, 2008;Zhu et al, 2008;Johnson et al, 2009;Xue et al, 2009). However, rice small RNA targets were mainly predicted via computational approaches, and only a small proportion of targets have been validated experimentally (Sunkar and Zhu, 2004;Sunkar et al, 2005;Yang et al, 2006;Liu et al, 2007a;Lacombe et al, 2008;Lu et al, 2008;Zhu et al, 2008;Liu et al, 2009).…”
Section: Introductionmentioning
confidence: 99%